2021
DOI: 10.3390/insects12070610
|View full text |Cite
|
Sign up to set email alerts
|

Are Dried and Powdered Moringa oleifera Lam. Leaves Susceptible to Moths That Feed on Stored Products?

Abstract: The leaves of Moringa oleifera are increasingly used as a food supplement in several countries due to their nutritional composition, which is rich in protein, vitamins, and mineral salts. Foodstuffs can be damaged by several pests when stored in environments with temperatures that are favorable to insect development; therefore, the susceptibility of M. oleifera leaves to attacks of moths that feed on stored products was tested. Tests were carried out on Pyralid Cadra cautella, Corcyra cephalonica, and Plodia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When nymphs of the house cricket, Acheta domesticus (L.), and the field cricket, Gryllus bimaculatus De Geer (Orthoptera: Gryllidae), were reared on diets supplemented with 10% of MO leaves, mortality rates were significantly higher compared to the control diet for both insect species tested [ 32 ]. A recent study that evaluated the susceptibility of MO leaves to Pyralid moths showed that both the powdered and the dried MO leaves were not susceptible to moth attacks, as they could not support larval growth for most of the moth species tested and this finding was mainly attributed to the presence of secondary metabolites in the MO leaves [ 12 , 13 , 14 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When nymphs of the house cricket, Acheta domesticus (L.), and the field cricket, Gryllus bimaculatus De Geer (Orthoptera: Gryllidae), were reared on diets supplemented with 10% of MO leaves, mortality rates were significantly higher compared to the control diet for both insect species tested [ 32 ]. A recent study that evaluated the susceptibility of MO leaves to Pyralid moths showed that both the powdered and the dried MO leaves were not susceptible to moth attacks, as they could not support larval growth for most of the moth species tested and this finding was mainly attributed to the presence of secondary metabolites in the MO leaves [ 12 , 13 , 14 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data on the effect of the addition of MO leaves into the diets of edible insects are limited. In one of the few studies available, the final weight of both A. domesticus and G. bimaculatus reared on feed supplemented with 10% MO leaves was significantly lower compared with the weight of larvae fed on the control feed, indicating a lower palatability for the MO feeds [ 33 ]. Overall, although the addition of the MO leaves powder into the diet of TM larvae marginally reduced larval survival, especially at high inclusion rates, it resulted in higher final larva weights, suggesting an improvement of the nutrient profile of the MO feeds compared to bran, which subsequently resulted in the increased larval growth and development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation